Implikasi Religiusitas dalam Alkitab Guna Membangun Kerukunan Umat Beragama Sebagai Tujuan Misi Kristen di Indonesia - Iky Sumartina Putri Prayitno; K Katarina; Theresia Tiodora Sitorus (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
This study aims to describe Christian attitude in maintaining the harmony of the Republic of Indonesia throught acts of love, as written in Romans 12:9-10. Love is the main commandment that every Christian should have in his life and this is the core of the teaching of Jesus Christ. Love is the calling of every Christian’s life. Through acts of love, every Christian can accept, love, and respect others, regardless of the differences that other people have, including the beliefs one has. This shows that harmony can be maintained and maintained in the Unitary State of the Republic of Indonesia, if every Christian applies acts of love in his life. The act of love in this study, the authors describe through qualitative-descriptive research with the literature study method. In addition, the author also uses the biblical hermeneutic method to find the meaning and form of acts of love that can care for and maintain the harmony of thr Republic of Indonesia based on Romans 12:9-10. Based on the analysis of the text Romans 12:9-10, the author finds that the acts of love that are focused on in this verse, to maintain the harmony of the Unitary State of the Republic of Indonesia are sincere love or love that does not pretend, love that does good, and love that precedes respect.